Methods for building geo-social systems in the internet. Cartographic and geo-location services - Каук, Виктор Иванович; Дубровский, Александр (Eastern-European Journal of Enterprise Technologies, 2010)
Features of geo-services are discussed; the analytical overview such kind of services is listed. Web-service for demonstration of analysis results is reviewed.